Solution scattering approaches to dynamical ordering in biomolecular systems - Bernadó, Pau; Shimizu, Nobutaka; Zaccai, Giuseppe; Kamikubo, Hironari; Sugiyama, Masaaki (Biochimica et biophysica acta, 2018)
Clarification of solution structure and its modulation in proteins and protein complexes is crucially important to understand dynamical ordering in macromolecular systems. Small-angle x-ray scattering (SAXS) and small-angle neutron scattering (SANS) are among the most powerful techniques to derive structural information. Recent progress in sample preparation, instruments and software analysis is opening up a new era for small-angle scattering. In this review, recent progress and trends of SAXS and SANS are introduced from the point of view of instrumentation and analysis, touching on general features and standard methods of small-angle scattering. This article is part of a Special Issue entitled “Biophysical Exploration of Dynamical Ordering of Biomolecular Systems” edited by Dr. Koichi Kato. •Introduction of general theory and classical measuring methods of small-angle X-ray and neutron scattering; SAXS and SANS•Recent progress and trend of small-angle scattering from the viewpoints of instrumentation, analysis method and cutting edge results.•Introduction of SEC-SAXS methods•Recent progress of 3D modeling with SAXS data•Application of contrast variation and deuteration technique for protein systems with SANS